Conservation and restoration works of the Four Sewers Fountain in Daganzo (Madrid, Spain) - García Alcocer, Vanesa; Juste Ballesta, José; Soria Hernanz, Elsa (Ge-conservacion, 2017)
The paper’s field focuses on the Restoration of the Four Sewers Fountain of Daganzo and the improvement of its immediate environment, linked to the Plan of Fountains and Historical Gardens of the Regional Government of Madrid. Historically, this element has been a reference at a territorial level, being part of troughs net and cattle trails for livestock, besides urban scale, serving public utility and point of drinking water supplying for the village. The intervention has had a dual purpose. On the one hand, monument’s enhancement, recovering the original presence of the Fountain, altered after paving works of the square in 1985, which left it half-buried. On the other hand, recuperating the memory of the laundry, demolished on the same date, making it the main character of a new public space created around the pylon, which recovers its social role as meeting place for neighbors. This process has benefited from a deep archival previous research; documentation, conservation and display of archaeological remains discovered; and a thorough restoration work to return its values to this Cultural Heritage Property.